DC performance and AC loss of sub-size MgB2 CICC conductor for fusion magnet application. (1st May 2022) - Gao, P.; He, Y.X.; Ma, H.J.; Anvar, V.A.; Huang, J.F.; Pan, X.F.; Zhou, C.; Nijhuis, A.; Li, J.G.; Qin, J.G.; Wang, W. J.; Yu, M.; et al.
Abstract: Given the low price and relatively high transition temperature (39 K) of MgB2 conductor, MgB2 -based superconductors are a potential candidate for the lower field fusion coils, such as poloidal field (PF) coils, correction coils and feeders. However, to date, the application of MgB2 is limited to demonstrators in a low magnetic field of up to 5 T and at temperatures of up to 10 to 20 K, relying on cryogen-free, helium gas or liquid hydrogen cooling, which significantly reduce the cost of cryogenic systems. To demonstrate the feasibility and performance verification of large size MgB2 PF conductors based on ITER and CFETR requirements, a 4th-stage subsize MgB2 cable-in-conduit conductor (CICC) cable sample is made at the Institute of Plasma Physics, Chinese Academy of Sciences. The CICC contains 96 in situ MgB2 superconducting wires, manufactured by Western Superconducting Technology Ltd. and 48 copper wires. The critical current of the sub-size cables and MgB2 witness wires are examined with different background magnetic fields at 4.2 K. In addition, the AC loss is measured utilizing magnetization and calorimetric methods. To further clarify the influence of electromagnetic force on the AC loss performance, the cable sample is pressed transversely at room temperature and then inserted into a dipole magnet for AC loss measurement at 4.2 K. The critical current at 4.2 K of the subsize MgB2 CICC cable shows 20% degradation compared to the witness wires at 2 T background magnetic field. However, no further critical current degradation is visible during ramping up and down the magnetic field. The coupling loss time constant for 1 T background magnetic field amounts to 480 ms. No significant effect of the applied transverse stress on the coupling loss is observed between 0 and 10 MPa.